UNDERSTANDING YOGASUTRA: A FRAMEWORK FOR ECOLOGICAL VIRTUE ETHICS - Sreevidya, P.S. (International Journal of Research -GRANTHAALAYAH, 2017)
This is an endeavor to seek the possibilities of the application of ethical principles of yoga in present day of ecological issues. The relevance of this research paper is evident from the fact that ecological issues are not only scientific but also an ethical and this research paper is reliable and informative in the extent that it seeks to challenge the existing relationship between human beings and nature with the description of the present crisis of ecology as a crisis of human-nature relationship. To talk of ecological issues signifies that most of the issues may occur because of the attitude and behavior patterns of man towards environment. The confluence of ethical principles of yoga and ecology offer profoundly relevant response to the ecological issues and brings forth an ecological virtue ethics, which care for all natural entities with main focus of the relationship between man and environment. It offer systematic framework for understanding the traits of character and types of action that cause problems for environment. Yoga approach on ecology is intrinsic in nature, which includes moral expansionism that tries to expand outward from human centered ethics towards animals and sentient life in general. All life forms of plants and animals are interrelated and have an intrinsic value. Ethical principles of yoga give greater importance to the attitude of the mind rather than on postulation of the elaborate theories of what is right and wrong. So the virtues of yoga ethics would be used as a remedy towards changing an attitude of the common man towards his environment.